Tinjauan Yuridis terhadap Pelaku Tindak Pidana Penyebaran Uang Palsu - Eko Nurisman; Stella Monica (Journal of Judicial Review, 2018)
This research is expected to understanding how the Judge considerates the sanctions to criminals who counterfeit money. As well as the ways to prevent the crimes in counterfeiting money. The normative empirical method is used in this research, which is a research method that collects the data based on the regulations and written laws, the literature of study and supported by the interview’s results as the supporting data. The data then will be analyzed, arranged and be explained descriptively for gaining the conclusions from that data analysis result. The conclusion of this research is that the Judge will use three theories to give judgment for counterfeit money criminal. The theories such as Absolute Theory, Relative Theory, and Mix Theory. This kind of case can use the Preemptive, Preventive, and Repressive efforts to prevent the counterfeit money act.